(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Maintenance in civil engineering is a very important topic. Since the aging of different constructions and structures is a problem of concern from a civil engineers point of view. The paper discusses and reviews forms of constructions and maintenances performed in civil engineering as well as economic analysis of cost or value proposition to these different forms are also discussed in brief.